Increasing skin self-examination after melanoma: an intervention using text and tablet delivery - Marie Johnston (Frontiers in Public Health, 2015)
Background: Following surgery for melanoma, there is a high risk of recurrence and it is recommended that patients perform regular total skin self-examination (TSSE) to complement physician follow-up. However practice is sub-optimal and reported barriers to TSSE include lack of training, waning motivation and the time required. The Achieving Self-directed Integrated Cancer Aftercare (ASICA) intervention was developed based on behaviour change theory [Information-Motivation-Behavioural skills model (IMB) and Control Theory]. Aims: This study assessed acceptability and feasibility of ASICA. Methods: The intervention involves text message prompts from the nurse-lead (N), information and TSSE demonstration by tablet, monitoring of TSSE, photographing any skin changes and sending to N via tablet, feedback and follow-up by N. Interviews were conducted with 21 people previously treated for cutaneous melanoma. The intervention was piloted with 20 people treated for melanoma. Results: Interviewees were positive about the use of technology to remind and instruct on TSSE, conducting it in their homes and getting feedback quickly. Pilot participants were strongly positive; 15 adhered well to the intervention, 4 intermittently and one withdrew. Symptoms were reported by seven and two had further surgery, one with a recurrent melanoma. Several practical issues were identified. Participants’ intention and self-efficacy increased. Conclusions: The ASICA intervention was acceptable to most patients and feasible following small technical adjustments. It is now proposed to evaluate the intervention in a randomised controlled trial.